Two Individuals with Rare Blocked Antigen Phenomenon and Coinciding Warm Autoantibody Mimicking Alloanti-Jk3 Resolved with JK Analysis. (28th October 2021) - Zinni, J G; Mullins, D; DeChristopher, P J; Ramsey, G; Vission, B; Stef, M
Abstract: Introduction/Objective: Kidd antigens can bind complement (C3) as well as Kidd specific warm autoantibodies (WAAb). An 838G>A single nucleotide variant (SNV) defines JK*01 and JK*02 which codes the antithetical Jka and Jk b, respectively. Both alleles translate the high prevalence (>99%) Jk3 (JK3). The 130G>A is associated with weak Jka and weak Jkb expression. In vivo binding of non-agglutinating globulins can cause false-negative phenotypes by means of the blocked antigen phenomenon (BAP). Methods/Case Report: Transfusions were requested for a 74-year-old Caucasian (CA) female with Evan's Syndrome, and an 85-year-old African American (AA) female with metastatic uterine cancer. Both had a history of nonspecific WAAb. Direct antiglobulin testing (DAT) detected moderate in vivo sensitization of IgG and C3. They phenotyped Jk(a- b-) with untreated and EDTA glycine-acid (EGA) treated IgG DAT-negative cells. Their serum contained anti-Jk3 reactivity, while a panreactive WAAb in the eluate reacted with Jk3- donor and EGA treated DAT-negative autologous cells. Weak anti-Jka and anti-Jkb reactivity remained in the alloadsorbed serum of the antithetical adsorbing cells. Genetic testing of the CA revealed JK*01W.01(130A)/02 alleles, while cDNA confirmed the alleles would be transcribed into mRNA. Sequencing of the AA detected 130G/A, and 838G/A as well as other silent mutations predicting either a Jk(a+wb+) or Jk(a+b+w) phenotype. The CA received one compatible JK:-3 transfusion, and both individuals benefited from multiple least incompatible transfusions of Jk a+ and/or Jk b+ donors with expected hemoglobin increases (1 g/dL per transfusion). The CA serologically phenotyped Jk(a-b+) 132 days later following prolonged immunosuppressive therapy while a normocytic normochromic anemia and the WAAb persisted. No follow up evaluations of the AA are available. Results (if a Case Study enter NA): NA Conclusion: Unexpected BAP can confound immunohematology testing and lead WAAbs mimicking alloanti-Jk3 to be mischaracterized as allogeneic. By predicting phenotypes, genetic analysis can aid serological techniques in antibody characterization and help circumvent complications searching for rare JK:-3 donors.